2022
DOI: 10.1007/s11469-022-00844-8
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Shopping Behavior: An Item Response Theory Examination of the Seven-Item Bergen Shopping Addiction Scale

Abstract: There has been an increasing amount of research examining problematic shopping behavior (PSB), often referred to in the psychological literature as “compulsive buying” or “shopping addiction.” A popular scale for assessing the risk of PSB is the seven-item Bergen Shopping Addiction Scale (BSAS). To expand our knowledge of the psychometric properties of this instrument, the present study employed Item Response Theory (IRT) and differential item functioning analyses (DIF) while concurrently attempting to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…In line with previous studies, questions addressing relapse (i.e., inability to cut down) assume the awareness of problematic behaviors and intent of cutting down, yet the limited reliability observed here may suggests that individuals within 0SD to +2SD in PSMU may not perceive their social media use as problematic (i.e. lacking reflection), and thus not intent to reduce it ( Zarate, Fullwood, Prokofieva, Griffiths, and Stavropoulos, 2022 ). Additionally, none of the items provided sufficient information to reliably identify individuals with significantly low levels of PSMU (−3SD to −2SD).…”
Section: Discussionsupporting
confidence: 85%
“…In line with previous studies, questions addressing relapse (i.e., inability to cut down) assume the awareness of problematic behaviors and intent of cutting down, yet the limited reliability observed here may suggests that individuals within 0SD to +2SD in PSMU may not perceive their social media use as problematic (i.e. lacking reflection), and thus not intent to reduce it ( Zarate, Fullwood, Prokofieva, Griffiths, and Stavropoulos, 2022 ). Additionally, none of the items provided sufficient information to reliably identify individuals with significantly low levels of PSMU (−3SD to −2SD).…”
Section: Discussionsupporting
confidence: 85%
“…Using these steps, a five-factor ESEM was fitted with all non-primary items approximating zero (~ 0). This model showed acceptable fit indices (χ 2 [185] = 1372.931, p < 0.001, CFI = 0.952, TLI = 0.922, RMSEA = 0.041), most items loaded significantly on all five latent factors and latent factors covaried (see Fig. 4).…”
Section: Fig 2 Sdq Models Proposed In Previous Literaturementioning
confidence: 99%
“…Human behavior researchers commonly employ selfreport scales to assess individuals' experiences, including complex psychiatric presentations [1,2]. Such instruments usually include items or indicators assumed to capture latent constructs [3].…”
mentioning
confidence: 99%
“…Previous literature has identified gender differences in an individual's propensity to develop certain types of addictive behaviors (Charzyńska et al, 2021;Chen et al, 2017;McHugh et al, 2018;Pelissier & Jones, 2005;Pontes et al, 2019;Tang & Koh, 2017). For example, while males are more vulnerable to developing substance, gaming, gambling, and online porn consumption-related addictions, females appear more likely to experience problematic behaviors associated with excessive use of social networking sites, shopping, and even studying (Charzyńska et al, 2021;McHugh et al, 2018;Pelissier & Jones, 2005;Pontes et al, 2019;Zarate, Fullwood, et al, 2022). Similarly, research has indicated that there may be gender differences in the age of onset of such problematic behaviors, especially for behavioral addictions (e.g., gambling), with females more likely to have a mid-to-later life onset and males commonly displaying earlier difficulties (APA, 2013).…”
Section: Gender Differencesmentioning
confidence: 99%
“…Thus, Mood modification to avoid distress or social isolation could increase the likelihood of transitioning into other problematic online behaviors. Moreover, studies reported that individuals might develop problematic behaviors such as online gaming (Gomez et al, 2018), problematic online shopping (Zarate, Fullwood, et al, 2022), or disordered online gambling (Stavropoulos, Monger, et al, 2022) to "escape" their problems (i.e., Mood modification). Finally, the results presented here support the hypothesized "digital convergence", suggesting that certain features of online platforms may facilitate further problematic online behaviors (Delfabbro & King, 2020).…”
Section: Network Structure Of Online Problematic Behaviorsmentioning
confidence: 99%